Management information systems : a study of computer-based information systems - McLeod, Raymond (Maxwell Macmillan Canada, 1993)
pt. 1. Information as a Resource. Ch. 1. Introduction to Information Management. Ch. 2. Using Information Technology for Competitive Advantage pt. 2. Information Methodologies and Tools. Ch. 3. The General Systems Model of the Firm. Ch. 4. The Systems Approach. Ch. 5. The System Life Cycle. Ch. 6. Tools of Systems Planning, Analysis, and Design. Ch. 7. Tools of Systems Implementation, Audit, and Control pt. 3. Information Technologies. Ch. 8. Computer Fundamentals. Ch. 9. The Database and Database Management System. Ch. 10. Telecommunications pt. 4. The Computer-Based Information System. Ch. 11. The Data Processing System. Ch. 12. The Management Information System. Ch. 13. Decision Support Systems. Ch. 14. Office Automation Systems. Ch. 15. Artificial Intelligence and Expert Systems pt. 5. Organizational Information Systems. Ch. 16. Executive Information Systems. Ch. 17. Marketing Information Systems. Ch. 18. Manufacturing Information Systems. Ch. 19. Financial Information Systems. Ch. 20. Human Resource Information Systems pt. 6. Issues and Trends. Ch. 21. Current issues and Trends in Information Systems